OPERASIONALISASI PRODUK BAI’ AL-MURABAHAH DALAM PERBANKAN SYARI’AH - Sukandi; Syarifuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
Murabahah sale and purchase is a form of buying and selling in which theseller informs the buyer aboutn the cost of goods (capital) of the goodsand the buyer, buys it based on the principil price, then provides theseller with profit according todeal.Regarding the agreed profits, the seller must notify the buyer of thepurchase price of the goods and state the amount of profit added to thefee. Murabahah contract is good to practice because it will save frompracticeusury. Surely it must be realized according to syara’ rules.